2023
DOI: 10.1007/s12273-022-0982-0
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin of large respiratory droplets by their deposition characteristics inside the respiratory tract during speech

Abstract: Origin of differently sized respiratory droplets is fundamental for clarifying their viral loads and the sequential transmission mechanism of SARS-CoV-2 in indoor environments. Transient talking activities characterized by low (0.2 L/s), medium (0.9 L/s), and high (1.6 L/s) airflow rates of monosyllabic and successive syllabic vocalizations were investigated by computational fluid dynamics (CFD) simulations based on a real human airway model. SST k-ω model was chosen to predict the airflow field, and the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…By applying a three-mode droplet size distribution coupled with a mode-dependent viral load, 23,32 we find that exhaled droplets with d 0 ≤ 10 μm play a more important role in airborne transmission than larger droplets. This observation aligns with recent findings presented by Y. Wang et al 44 The droplet size-dependent virus concentration in exhaled breath air is shown in Fig. 2.…”
Section: Resultssupporting
confidence: 93%
“…By applying a three-mode droplet size distribution coupled with a mode-dependent viral load, 23,32 we find that exhaled droplets with d 0 ≤ 10 μm play a more important role in airborne transmission than larger droplets. This observation aligns with recent findings presented by Y. Wang et al 44 The droplet size-dependent virus concentration in exhaled breath air is shown in Fig. 2.…”
Section: Resultssupporting
confidence: 93%